Clarifying the meaning of a knowledge-rich approach to curriculum design: a social realist perspective - McPhail, Graham (Curriculum perspectives, 2025)
The CDC Model is as a design response to the problem of the disconnect between conceptual knowledge (‘knowledge-that’) and applied knowledge (‘know-how-to’) and to the challenge of learning to think abstractly and generalise from concepts. Laudable aspects in the AERO report include recognition of the danger of a generic competencies and skills approach as the foundation for curriculum (2024, p. 4), as well as noting the strong equity dimension of a knowledge-rich approach (p. 8). [...]the report highlights the importance of teacher subject knowledge, progression in curriculum design, and notes some significant features derived from the evidence base of cognitive science that can guide pedagogy (e.g. practise, review, retrieval, p. 4). The concept of knowledge-rich needs more elaboration in terms of its constituent parts: concepts, content, and skills, so in the remainder of this opinion piece I focus on two aspects of curriculum design that I suggest are most significant in an approach that is truly knowledge-rich. The key point here is that it is this systemised structure of concepts that is the key to understanding a subject or topic as more than a collection of specialised terms, ideas, procedures, and content, and it is this systemised structure of concepts that we need to understand as we design curricula for teaching.